2014
DOI: 10.1371/journal.pgen.1004055
|View full text |Cite
|
Sign up to set email alerts
|

The Candidate Splicing Factor Sfswap Regulates Growth and Patterning of Inner Ear Sensory Organs

Abstract: The Notch signaling pathway is thought to regulate multiple stages of inner ear development. Mutations in the Notch signaling pathway cause disruptions in the number and arrangement of hair cells and supporting cells in sensory regions of the ear. In this study we identify an insertional mutation in the mouse Sfswap gene, a putative splicing factor, that results in mice with vestibular and cochlear defects that are consistent with disrupted Notch signaling. Homozygous Sfswap mutants display hyperactivity and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…The Jag1 ligand is also expressed in the cochlear duct as the first hair cells differentiate (Figure 1C), and later in supporting cells (Morrison et al, 1999; Woods et al, 2004). Jag1 heterozygous mice also have increased inner hair cells (Kiernan et al, 2007; Moayedi et al, 2014), and we observed a similar phenotype of duplication of inner hair cells and inner phalangeal cells in Jag1 heterozygous mice (Figure 3A,B). We also confirmed that loss of both Lfng and Mfng led to a reduction in Notch signaling directly, by comparing N1ICD staining in Lfng;Mfng embryos to wild type controls (Figure 4A).…”
Section: Resultssupporting
confidence: 75%
“…The Jag1 ligand is also expressed in the cochlear duct as the first hair cells differentiate (Figure 1C), and later in supporting cells (Morrison et al, 1999; Woods et al, 2004). Jag1 heterozygous mice also have increased inner hair cells (Kiernan et al, 2007; Moayedi et al, 2014), and we observed a similar phenotype of duplication of inner hair cells and inner phalangeal cells in Jag1 heterozygous mice (Figure 3A,B). We also confirmed that loss of both Lfng and Mfng led to a reduction in Notch signaling directly, by comparing N1ICD staining in Lfng;Mfng embryos to wild type controls (Figure 4A).…”
Section: Resultssupporting
confidence: 75%
“…Despite the important role of alternative splicing in the formation of the cochlear tonotopic gradient ( Navaratnam et al, 1997 ; Rosenblatt et al, 1997 ; Miranda-Rottmann et al, 2010 ) and in hair cell development and function ( Kollmar et al, 1997 ; Liu et al, 2007 ; Webb et al, 2011 ) to date only two alternative splicing factors have been implicated in hearing: Srrm4/nSR100 ( Nakano et al, 2012 ) and Sfswap ( Moayedi et al, 2014 ). Both are expressed in hair cells necessary for the development of the sensory epithelium, in contrast with Nova1 and Nova2 , which are the first neuron-specific splicing factors described to regulate cochlear innervation.…”
Section: Discussionmentioning
confidence: 99%
“…The coordinated expression of these splicing-regulatory networks is due in large part to the selective activity of specialized RNA binding proteins that mediate the inclusion or exclusion of alternatively spliced exons based on their recruitment to cis acting elements in target transcripts (Chen and Manley, 2009; Fu and Ares, 2014). Consequently, mutations that disrupt either the cis or trans regulators of alternative splicing contribute significantly to human disease (Cieply and Carstens, 2015; Xiong et al, 2015; Li et al., 2016), as well as hearing loss in mice (Nakano et al, 2012; Moayedi et al, 2014). …”
Section: Introductionmentioning
confidence: 99%